Haemostasis and prevention of bleeding related to ER: The role of a novel self‐assembling peptide. Issue 1 (1st February 2019) - Subramaniam, Sharmila; Kandiah, Kesavan; Thayalasekaran, Sreedhari; Longcroft-Wheaton, Gaius; Bhandari, Pradeep
Abstract : Background: Endoscopic resection is now commonly used for removal of early gastrointestinal lesions. However, the risk of the procedure may be heightened by intraprocedural or delayed bleeding. A novel, self‐assembling peptide (PuraStat®) was recently licensed for use as a haemostat. Objective: The aim of this study was to assess the efficacy and safety of this haemostat when used to control intraprocedural bleeding or to prevent delayed bleeding in endoscopic resection. Methods: PuraStat® was used on 100 patients undergoing endoscopic resection in a tertiary referral centre. The efficacy, safety, feasibility of use and delayed bleeding rates were measured. Results: Forty‐eight oesophageal, 31 colorectal, 11 gastric and 10 duodenal procedures were included. The mean lesion size was 3.7 cm and 30% of the patients were on antithrombotic therapy. Intraprocedural bleeding occurred in 64%. PuraStat® was an effective haemostat in 75% of these cases. Only a small amount was required for haemostasis (mean = 1.76 ml) and it took on average 69.5 seconds to stop a bleed. The delayed bleeding rate was 3%. Conclusions: PuraStat® is an effective haemostat for use in controlling bleeds during endoscopic resection. It is safe, easy to use and did not interfere with the procedure.